Removing relative age effects from youth swimming: The development and testing of corrective adjustment procedures - Cobley, S.; Abbott, S.; Eisenhuth, J.; Salter, J.; McGregor, D.; Romann, M. (Journal of Science and Medicine in Sport, 2019)
Objectives: (1) Generate accurate estimates of the relationship between decimal age (i.e., chronological and relative) with swimming performance based on longitudinal data. (2) Determine whether corrective adjustment procedures can remove Relative Age Effects (RAEs) from junior/youth swimming.